The Translation of Ideologies in the English â Indonesian Translation of Twains âThe Adventure of Tom Sawyerâ - Rochmawan, Muhammad Rizky; Yuliasry, Issy; Wuli Fitriati, Sri (English Education Journal, 2018)
This thesis was focused on the rendering of ideologies in the English â Indonesian Translation Twainâs The Adventure of Tom Sawyer. The main purposes of the study was to explain the rendering of ideologies found in the English â Indonesian translation in the Twainâs novel The Adventure of Tom Sawyer which was realized through the rendering of ideologically-contested words, nominalization and voice. This study used descriptive qualitative study by means of Critical Discourse Analysis framework proposed by Fairclough (1989). The analysis was done by analyzing the ideologically-contested words, nominalization and voice found in the sentences where ideologies were embedded. This was also done by getting through the analysis of micro-level, meso-level and macro-level of Critical Discourse Analysis. The results of the study showed the way the ideological differences between the source language and target language were renderred, such as: tacit assumption, belief system and value system. Most of the ideologies were rendered into target language, while only few were shifted as the result of choosing the words, nominalizing the clause and changing the voice. The results of the study are expected to give a valuable contribution to the translator, English Department students and lecturers and writers to consider the rendering of ideologies in the literary works, in order to raise ideological awareness embedded on the source language and to succeed rendering the ideologies by considering the socio-cultural condition.